SiHLEWeb.com: Development and Usability Testing of an Evidence-Based HIV/STI Prevention Website for Female African-American Adolescents - Danielson, Carla Kmett (Health Informatics J, 2014)
African-American adolescent girls are at disproportionate risk for HIV infection. Although numerous evidence-based risk-reduction interventions exist, dissemination and implementation resources remain limited, and prevention services remain notably inaccessible to the very populations at highest risk for HIV infection. Internet delivery of HIV risk-reduction programming has promise as a mechanism for extending the reach of existing prevention efforts and overcoming barriers associated with traditional service delivery. This article: (1) details the development process for the creation of SiHLEWeb, a web-adapted version of an evidence-based, culturally-informed HIV prevention program traditionally delivered to female African-American adolescents via an in-person group format; and (2) presents findings from quantitative and qualitative usability testing conducted among 18 African-American girls (13–18). Results suggest that users found the website improved knowledge and learning, was helpful, efficient to use, and generally attractive. Users reported some concerns about website navigation. Implications for internet delivery of health prevention programming are discussed.